INTERPRETASI AKUNTANSI DARI PERSPEKTIF UMKM BATIK DI KOTA MALANG - Ningsih, Ayu Agus Tya; Gunawan, Tegar (Magister Manajemen Universitas Wisnuwardhana, 2023)
Abstract. This study intends to investigate how Malang City batik artisans perceive accounting by keeping track of business activity. This study used a qualitative methodology, a natural setting as a data gathering tool, inductive analysis, and a meaning-centered approach. Researchers employed an interpretive paradigm in this investigation.